Analisis Kecepatan Kendaraan Akibat Hambatan Samping (Studi Kasus: Jl. Mayor Abd. Karta Wirana Kota Jambi di sekitar Lippo Mall) - Emelda Raudhati; Ellyta Mona (Universitas Batanghari, 2020)
This study aims to analyze the vehicle speed due to side friction with the MKJI 1997 method and the analysis of the cumulative distribution of speed using statistical methods. This research was conducted on Jalan Mayor Abd. Karta Wirana Jambi City around Lippo Mall. The results show that the total side friction for events per day on Wednesday is 1175.34 with the lowest incidence of resistance on pedestrians at 48.39 and the highest incidence of friction on incoming and outgoing vehicles of 790.32. Side friction class on Jalan Mayor Abd. Karta Wirana, according to MKJI 1997, is in a high class (VH) with a frequency of weight events exceeding > 900 events per day. While the speed when disturbed is obtained an average of 11, 56 km / hour is at the lowest speed interval 10 - 11 km / hour and the highest speed is 12 - 13 km / hour. The average of undisturbed speed of 30.32 km / h at the lowest speed interval of 20-24 km / hour and the highest is 36-40 km / hour. The difference between these two speeds states that the side drag has a very large effect on speed (a very significant decrease in speed is 61.87%)